If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -24 + -6x + -24 = 5x + 6 Reorder the terms: -24 + -24 + 12x + -6x = 5x + 6 Combine like terms: -24 + -24 = -48 -48 + 12x + -6x = 5x + 6 Combine like terms: 12x + -6x = 6x -48 + 6x = 5x + 6 Reorder the terms: -48 + 6x = 6 + 5x Solving -48 + 6x = 6 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -48 + 6x + -5x = 6 + 5x + -5x Combine like terms: 6x + -5x = 1x -48 + 1x = 6 + 5x + -5x Combine like terms: 5x + -5x = 0 -48 + 1x = 6 + 0 -48 + 1x = 6 Add '48' to each side of the equation. -48 + 48 + 1x = 6 + 48 Combine like terms: -48 + 48 = 0 0 + 1x = 6 + 48 1x = 6 + 48 Combine like terms: 6 + 48 = 54 1x = 54 Divide each side by '1'. x = 54 Simplifying x = 54
| 3y^2=5-4y | | 3-[8-(x-9)]=3(x-2) | | 22-6x=4-3x | | -2x-7=-8x-10 | | q(x)=x^4-4x^3+8 | | x^2+30x=1000 | | 3(9s+1)-18s=3(3s+1)-7 | | x(x+5)=2+55 | | 3+2x=5x-6 | | -6x-2=4x-35 | | -3(s+2)=-2(s+4)-s | | 4(2x-3)=-(2+3x)+5 | | 15x^2-17y+11x=0 | | 4x-(5-x)=20 | | d/14-9=5 | | 9x=x^2+4 | | 9x^2+64=0 | | 6(3x-4)-4(2x-13)=9x+6 | | 8x-5=4x-25 | | 2x^4+7x^3-4x^2-45x-50=0 | | (20+x)(20-x)=0 | | 6x-12x=66 | | 7y+2=6y-6 | | 9x^2+1=12x | | 5x-7=8+2x-3 | | (6x+3)-(2x-4)= | | 6x-12x=66x | | 5+7x=4x+5 | | 6-12x=66 | | 121m^2-9p^2=0 | | 6(x-12)=66 | | 6y^2=200 |